Fracture, Fatigue, Failure and Damage Evolution, Volume 6 Proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics - Carroll, Jay; Xia, Shuman; Beese, Allison M.; Berke, Ryan B.; Pataky, Garrett J. (Conference Proceedings of the Society for Experimental Mechanics Series, 2019)
Fracture, Fatigue, Failure and Damage Evolution, Volume 6 of the Proceedings of the 2018 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the sixth volume of eight from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Novel Experimental Methods Extreme Environments Interfacial Fracture Integration of Models & Experiments Mechanics of Energy & Energetic Materials Integration of Models & Experiments In Situ Techniques for Fatigue & Fracture Microscale & Microstructural Effects on Mechanical Behavior.